Genetic basis of infertility - Özbey, Ülkü; Yüce, Hüseyin; Elyas, Halit (My University, 2006)
Infertility is defined as the inability to conceive after one year of regular intercourse without contraception. Infertility is a significant medical problem that affects many couples. The prevalence of infertility is estimated between 12 and 14% and remains stable in recent years. It thus represents a common condition, with important medical, economic and psychological implications. According to a standard protocol, infertility evaluation usually identifies different causes, including, male infertility (30 %), female infertility (35%), the combination of both (20%), and finally unexplained or "idiopathic" infertility (15%). Many cases of idiopathic infertility have a genetic or molecular basis. Female causes of infertility comprise endometriosis, tubal damage and ovulatory dysfunction (OD). In men, the main causes of infertility are oligospermia, asthenospermia, teratozoospermia and azoospermia, which accounts for 20-25% of cases. Genetic causes of infertility can be broken into Y chromosome deletions (specifically deletions in the AZF a, b, and c regions), single gene disorders (particularly those relating to the CFTR gene), multifactorial causes and chromosome abnormalities. Males contribute to about 50% of infertility in humans and Y chromosome deletions are the major known genetic contributions. Preconception genetic evaluation and counseling can help infertile couples maximize their chances of delivering a healthy baby. Counseling should begin with a thorough history, including medical, social, reproductive and genetic histories of both partners. The present review provides an overview of the causes of human infertility, particularly the molecular basis of male infertility.
İnfertilitenin genetik temelleri
Keywords: transmembrane conductance regulator; anamnesis; asthenospermia; azoospermia; chromosome deletion Y; counseling; economic aspect; endometriosis; female infertility; genetic disorder; heredity; human; infertility; male infertility; oligospermia; ovary insufficiency; review; social aspect